Strategic Management of Public Relations Communication in Islamic Educational Institution - Astarina, Risna; Sa’diyah, Maemunah; Sastra, Ahmad (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2026)
The decline in student enrollment poses a significant challenge for Islamic educational institutions, including SMP Qur’an As-Salam Bogor, highlighting the need for effective organizational communication management. This study aims to analyze Public Relations (PR) strategies in managing communication and their contribution to strengthening the school’s public image. This research employed a qualitative case study approach, with the research subjects consisting of school leaders, teachers, PR officers, and community representatives. Data were collected through in-depth interviews, participatory observation, and documentation, and analyzed using Miles and Huberman’s interactive model, including data reduction, data display, and conclusion drawing. The results indicate that internal communication management is implemented through coordination meetings, task distribution, and collaboration among school stakeholders, while external communication focuses on activity publications, achievement promotion, and partnerships with the community and external institutions. These strategies contribute to a positive institutional image, increased public trust, and growing community interest in student enrollment. The study concludes that PR functions as a strategic connector between the school and its environment, extending beyond publication activities. It is recommended that Islamic schools optimize PR strategies using systematic and measurable communication approaches to enhance sustainability and competitiveness in the modern era.